Malay motifs in the National Mosque of Malaysia / Isra Mahmoud al Jarah - Isra Mahmoud, al Jarah (2017)
In most of the mosques in the Islamic world, motifs are part and parcel of their interior and external design. Motifs can be considered another instinct that craftsman inherited from Nature. The idea of motifs has evolved until the present time. Islamic Malay motifs also was particularly useful in documenting the early coming of Islam to Malaysia and its existence in the modern time. For example, the Motifs on Mosques in Malaysia shed light on the coming of Islam to that region and also general historical setting during the expansion of Islam. This research explores the Malay Motifs and attempt to address the important topic of Islamic motifs and its application in National Mosque in Malaysia as part of Islamic Malay decoration. There is no clear prohibition to decorate mosques, calligraphy and other motifs is allowed on condition that it is done with the intention of enhancing the respects and dignity of the mosque. In Malaysia, the exteriors and interiors of Mosques also have unique and different patterns of styles of Malay Art. The local Malay art sometimes work side by side with other Islamic foreign art to achieve the best results. Adopting the historical and descriptive research method, National Mosque from Malaysia was chosen in this research. This thesis is a significant contribution to the subject of Islamic Malay Art in Malaysia as well as the arrival and preservation of this heritage. Furthermore, this study would inspire other Malay Muslim artists in Malaysia to use Islamic motif in their work.